Competition in Nepalese Commercial Banks - Neupane, Bishnu Prasad (NRB Economic Review, 2016)
This study has made an attempt to assess the degree of competition (or market structure) in Nepalese commercial banking. For the purpose, both of structural (n-bank concentration ratio and Herfindahl-Hirschman Index) and non-structural measures (Panzar-Rosse H-statistics) have been used. Data of ten years have been abstracted from various sources for the analysis purpose. Study shows that the market structure of Nepalese commercial banks is characterized by the monopolistic competition. Further, it is observed that the banks other than government owned and joint-venture banks have been facing highest degree of competition where as joint-venture commercial banks face lowest degree of competition. Finally, the study suggested that the degree of competition among government owned, joint-venture and other Nepalese commercial banks slightly vary but overall market structure of all set of banks have the feature of monopolistic competition.